African American Consumers' Evaluations of Ethnically Primed Advertisements. Issue 1 (2nd January 2016) - Zúñiga, Miguel A.
Abstract : This study is a conceptual replication of Appiah and Liu (2009 ). Distinctiveness theory and social identity theory are used to study the effect of embedding African American cultural ethnic primes beyond the use of ethnic minority models in ads on ad attitude, brand attitude, and purchase intentions. Empirical results show that African American consumers respond significantly different when viewing a high African American cultural ethnic primed ad compared to a low and high white cultural ethnic primed ad (i.e., high, low = high, low levels of African American cultural ethnic primes found embedded in the ad). No significant responses from African American consumers were found when exposed to a high African American cultural ethnic primed ad versus a low African American cultural ethnic primed ad. This indicates it is not enough to include cultural ethnic primes beyond ethnic minority models to influence significantly different responses. This study recommends that situational and psychological factors (e.g., strength of ethnic identification, ethnic self-awareness, usage rate of cultural ethnic primes in media and geographic location of target audience, levels of ethnocentrism, and proportion of minority group to overall population in geographic location of target audience) need to be considered by marketers to increase ad effectiveness.